QUALITY AND HEALTH STATUS OF FARMER SAVED WHEAT SEED IN BANGLADESH - N. N. Tonu Md. Rafiqul Islam, Md. Masud Karim, M. Salahuddin M. Chowdhury; M A T Mia (International Journal of Research Science and Management, 2017)
Quality and health status of farmer saved wheat seed of cv Kanchan was determined by seed health and quality analysis. One hundred seed samples collected from 100 farmers representing ten upazilas under nine major wheat growing districts of Bangladesh were included. Seed health and quality analysis revealed that moisture content of farmer saved seed ranged between 12.04-13.30%. Six type’s seed contaminants– weed seeds, insects, varietal mixture, seed with husk, other crop seed and inert matter; and five types of abnormal seeds - black pointed seed, discoloured seed, undersized seed, shriveled seed and insect damaged seed, recorded in Farmer saved seed. On an average, 58.48% ‘clean’ or ‘best’ seed was recovered from farmer saved wheat seed by removing the seed contaminants and abnormal seeds through manual seed cleaning. Clean seed had the highest weight, while the undersized and black point Grade 5 seeds were lighter than all other categories of wheat seed. Of the 13 fungi encountered in farmers’ seeds, five target pathogenic fungi identified, in order of prevalence, were - Bipolaris sorokiniana, Alternaria tenuis, Curvularia lunata, Fusarium oxysporum and Aspergillus flavus. Incidence of these target fungi in both unclean and clean seeds varied significantly with respect to location of seed collection. All the five target fungal pathogens were more prevalent in farmers saved seed compared to clean seed. ‘Clean’ or ‘best’ seed significantly gave higher counts of normal seedlings and lesser percentage of abnormal seedlings and dead seeds over unclean farmers’ seed and abnormal seeds like black pointed, undersized, discoloured and shriveled seeds. Similarly clean seed resulted higher germination and seedling vigour index over unclean and abnormal seeds.